'It can't be found in books': how a flipped-classroom approach using online videos can engage postgraduate students in dissertation writing - Jessica Clare Hancock (Association for Learning Development in Higher Education (ALDinHE), 2019)
This article explores action research that introduced a flipped-classroom approach to teaching dissertation writing. The cohort involved postgraduates studying at master’s level, with a high proportion of international students. Dissertation writing had previously been taught in a lecture-based format, with limited time for activities. Moving some of the information-based content to online videos, which students were asked to watch before the teaching sessions, meant that face-to-face content could be entirely based around active learning and a social-constructivist approach. The students who experienced this flipped-classroom approach became more positive about the use of online videos during the teaching period. Many favourable comments were made about the videos, although several students appeared to prefer to use video content as a recap of face-to-face teaching, rather than appreciating a true flipped-classroom approach. Nevertheless, students agreed that the face-to-face activities helped put their learning from the videos into practice, the videos helped them to complete face-to-face activities, and that the teaching was beneficial for their dissertation writing abilities. Despite an absence of existing research for this context, a flipped-classroom approach to teaching dissertation writing is therefore recommended, as long as the students are fully briefed about the reasons for teaching in this way. This teaching method may be particularly beneficial for postgraduate students who are familiar with online learning through videos in earlier parts of their master’s level courses.